The hypothyroid (hyt/hyt) mouse: a model system for studying the effects of thyroid hormone on developmental changes in gene expression. - Green, R P (1988)
Thyroid hormone has been implicated as an important factor in rodent development. We have used a strain of mice with a recessive mutation producing congenital primary hypothyroidism (C.RF/J-hyt/+) to study the effects of thyroid hormone on developmental changes in the expression of genes encoding a number of proteins involved in lipid metabolism and transport. Total cellular RNA was prepared from the small intestine and liver of hyt/hyt mice and their unaffected littermates (+/?) at various times during postnatal development. RNA blots were probed with apolipoprotein A-I, A-II, A-IV, B, and E cDNAs plus cDNAs encoding the low density lipoprotein receptor, 3-hydroxy-3-methylglutaryl coenzyme A reductase, and three cytoplasmic hydrophobic ligand-binding proteins (two fatty acid-binding proteins and a protein that binds all-trans-retinol). Hypothyroidism results in small changes (1.5- to 5-fold) in the concentration of many of these mRNAs in liver and small intestine between postnatal days 15 and 50. A much greater tissue-specific effect was noted on apolipoprotein B (apoB) gene expression. In euthyroid +/? animals, apoB mRNA levels fall by a factor of 30 in liver between days 20 and 35 without a comparable decrease in the small intestine. This liver-specific decrease does not occur in hyt/hyt animals. The normal decrease in hepatic apoB mRNA levels is accompanied by a decrease in plasma apoB-100 but not apoB-48. No reduction in either form of plasma apoB was noted in hyt/hyt animals. Mutant hyt/hyt mice given thyroxine from birth to 35 days had liver apoB mRNA levels comparable to those in +/? littermates. In contrast, hepatic apoB mRNA concentrations did not fall to normal levels in hyt/hyt mice given thyroxine from postnatal days 15 to 35. All treatment groups have comparable levels of plasma corticosteroids. These data suggest that (i) there is a critical period or a required response time during postnatal development for thyroid hormone action on apoB gene expression, (ii) thyroid hormone's effect on apoB is tissue specific, and (iii) the hyt/hyt mouse represents a useful system to evaluate the developmental effects of thyroid hormone on specific gene expression.